2017
DOI: 10.5897/ajar2016.12083
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks in predicting energy density of Bambusa vulgaris in Brazil

Abstract: In this study, the physical and chemical characteristics of Bambusa vulgaris ex J.C. Wendl. var.vulgaris (Bambusa vulgaris) aged 1, 2 and 3 years were evaluated. The objective was to train, validate and evaluate the efficiency of artificial neural networks (ANNs) as predictive tools to estimate bamboo stem energy density grown commercially in northeastern Brazil. For that, samples were collected in a commercial plantation and managed for energy production, determining the energy properties. Among all the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Neural networks have also been shown to efficiently predict wood intrinsic characteristics such as moisture content (Ozsahin & Murat 2018), basic wood density , higher heating value (Estiati et al 2016), and energy density (Vale et al 2017), for which the aforementioned authors obtained better results than those reported in this study (RMSE% = 1.45%, R = 0.98, AD% = 0.14). However, those authors used basic wood density as a predictive variable.…”
Section: Modeling: Training Of Neural Networkmentioning
confidence: 44%
See 2 more Smart Citations
“…Neural networks have also been shown to efficiently predict wood intrinsic characteristics such as moisture content (Ozsahin & Murat 2018), basic wood density , higher heating value (Estiati et al 2016), and energy density (Vale et al 2017), for which the aforementioned authors obtained better results than those reported in this study (RMSE% = 1.45%, R = 0.98, AD% = 0.14). However, those authors used basic wood density as a predictive variable.…”
Section: Modeling: Training Of Neural Networkmentioning
confidence: 44%
“…Finally, the ANN that showed the best results was submitted to the validation process using the t-test and, subsequently, an aggregate difference in percentage (AD%), a statistical value used as indicator of under-or overestimation (Miguel et al 2015, Vale et al 2017. These analyses were conducted using the software Microsoft Excel 2013 ® (Microsoft Corp., Redmond, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANNs training was performed using the Intelligent Problem Solver tool from the Statistica 7.0 software [44]. This tool allows optimizing the ANN architecture by automatically setting the best number of neurons in the hidden layer and the best activation functions of the hidden and output layers, choosing the one with the least possible error, and is widely used by the scientific community [45][46][47]. https://doi.org/10.1371/journal.pone.0238703.g002…”
Section: Anns Trainingmentioning
confidence: 99%